Advances in the Molecular Mechanisms of Abscisic Acid and Gibberellins Functions in Plants 2.0 - Quesada, Víctor (2022)
Gibberellins (GA) and abscisic acid (ABA) are two phytohormones that regulate, in an antagonistic way, plant growth as well as several developmental processes from seed maturation and germination to flowering time, through hypocotyl elongation and root growth. In general, ABA and GA inhibit and promote, respectively, cell elongation and growth. Consequently, this mutual antagonism between GA and ABA governs many developmental decisions in plants.In addition to its role as a growth and development modulator, ABA is primarily known for being a major player in the response and adaptation of plants to diverse abiotic stress conditions, including cold, heat, drought, salinity or flooding. Remarkably, different works have also recently pointed to a function for GA in the control of some biological processes in response to stress.The selection of research and review papers of this book, mostly focused on ABA, covers a wide range of topics related to the most recent advances in the molecular mechanisms of ABA and GA functions in plants.